Pest categorisation of Satsuma dwarf virus. (31st October 2017) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Gregoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; Niere, Björn; Parnell, Stephen; et al.
Abstract: The EFSA Panel on Plant Health performed a pest categorisation of Satsuma dwarf virus (SDV) for the EU territory. SDV is a well‐known pathogen and the type species of the genus Sadwavirus in the family Secoviridae. SDV is now considered to include several other formerly distinct viruses which are therefore also covered in the present opinion. Citrus species and their relatives represent the main hosts of SDV and efficient diagnostic techniques are available. SDV is listed on some of its known hosts in Annex IIAI of Directive 2000/29/EC. It is transmitted by vegetative propagation of infected hosts and presumably through the soil, but the precise mechanism or vector(s) are still unknown. SDV is present in Asia and is not known to occur in the EU. Therefore, it does not meet this criterion to qualify as a Union regulated non‐quarantine pest (RNPQ). Plants for planting represent the main pathway for the entry, but this pathway is closed by existing legislation for the main hosts ( Citrus, Fortunella and Poncirus ). SDV is, however, able to enter the EU on plants for plants of its unregulated rutaceous or non‐rutaceous hosts. Should it be introduced, SDV has the potential to establish and subsequently spread with plants for planting and, possibly, through its poorly characterised natural spread mechanism(s). SDV is able to cause severe symptoms, quality and yield losses on a range of citrus crops. Overall, SDV meets all the criteria evaluated by EFSA to qualify as a Union quarantine pest. The main knowledge gaps and uncertainties concern (1) the potential significance of the unregulated rutaceous and non‐rutaceous hosts for virus dissemination and epidemiology, (2) the origin and trade volume of the plants for planting of these host imported in the EU and (3) the efficiency of natural spread of SDV under EU conditions.